Translating Igbo Gods into German, cultural distance and intercultural postcolonial communication (2024)
A culture’s gods provide insight into its cultural epistemologies, worldviews, establish its cosmologies and connection to the divine will, and detail the beliefs and values that form the basses of behavior, unity, and collective action of its people. The translation of gods is thus more than the exchange of information but also the representation of a people making it, therefore, the space for the contact, conflict and negotiation of cultural knowledge, values and beliefs, and differences, and for determining the international cultural standing of cultures. This study examined the translation into German of purposively selected Igbo god’s and divinities in Chinua Achebe’s classics Things Fall Apart (TFA) and Arrow of God (AOG) within the context of intercultural postcolonial textual communication/relations. Lawrence Venuti’s Domestication and Foreignisation translation approaches serve as framework while critical intercultural and translation analysis was descriptively applied to data.